A minimum facility method for in vitro collection of Digitaria eriantha ssp. pentzii and Cynodon dactylon - Ruredzo, T.J. (1991)
Simple in vitro techniques were developed for collecting Digitaria eriantha ssp. pentzii and Cynodon dactylon to obviate deterioration, quarantine and bulk problems of conventional methods for collecting vegetative material. Various antimicrobial agents were tested for effective surface- sterilisation of plant material and for supplementing the growth medium to reduce microbial contamination. Halazon tablets were used for surface-sterilisation and a combination of Rifamycine and Benlate was the most effective medium supplement. This technique was found useful for the field collection of vegetative germplasm of the 2 species. In field trials, 75% of D. eriantha spp. pentzii and C. dactylon cultures were aseptic and growing after 4 weeks in culture. The cultures were transferred to natural conditions in soil and approximately 70% of the 2 species were recovered as potted plants. In a field trial with C. dactylon, 92% of the cultures which had formed roots and 80% of the cultures which had no roots at the time of transfer to soil were successfully established as potted plants.